Inflammasome inhibitors: promising therapeutic approaches against cancer - Shengchao Xu; Xizhe Li; Yuanqi Liu; Yu Xia; Ruimin Chang; Chunfang Zhang (Journal of Hematology & Oncology, 2019)
Abstract Inflammation has long been accepted as a key component of carcinogenesis. During inflammation, inflammasomes are potent contributors to the activation of inflammatory cytokines that lead to an inflammatory cascade. Considering the contributing role of inflammasomes in cancer progression, inflammasome inhibitors seem to have a promising future in cancer treatment and prevention. Here, we summarize the structures and signaling pathways of inflammasomes and detail some inflammasome inhibitors used to treat various forms of cancer, which we expect to be used in novel anticancer approaches. However, the practical application of inflammasome inhibitors is limited in regard to specific types of cancer, and the associated clinical trials have not yet been completed. Therefore, additional studies are required to explore more innovative and effective medicines for future clinical treatment of cancer.